The effects of lead on antioxidants enzymes in children and the therapeutic/prophylactic role of antioxidants - Çaylak, Emrah; Halifeo?lu, Ihsan (My University, 2010)
Lead is a toxic metal, and is still present in our environment - in water, soil, and imported products manufactured with lead. Lead intoxication is the foremost environmental health threat to children in the world. Children are far more susceptible to lead neurotoxicity than adults because they absorb a higher fraction of lead and have a developing system of cell differentiation and growth that is more vulnerable to inhibition and damage. However, it has also been indicated that low-level exposures of lead result in cognitive dysfunction, neurobehavioral disorders, neurological damage, hypertension, and renal impairment. A common factor in the mechanism of all lead toxicities is oxidative damage. It increases production of free radicals and decreases availability of antioxidant reserves to respond to the resultant damage. The pathogenesis of lead toxicity is multifactorial, as interrupting enzyme activation, inhibiting trace mineral absorption, binding to sulfhydryl proteins, altering calcium homeostasis, and lowering the level of available sulfhydryl antioxidant reserves in the body. Calcium disodium EDTA and DMSA have been used as chelative agents for lead abatement in both adults and children. While chelation is the conventional recommendation for acute lead toxicity, chronic exposure is still under investigation. In addition to appropriate treatment for toxic metal exposure and accumulation, it is also important to minimize the effects of the metal. In this article, the role of antioxidants in the treatment of lead-related pathologies will be addressed.
Kurşunun çocuklardaki antioksidan enzimler üzerine etkileri ve antioksidanlarin tedavi edici/koruyucu rolü
Keywords: Antioxidant; Children; Lead; Oxidative stress